Potencial del turismo gastronómico del cantón Sigchos de la provincia de Cotopaxi. - Gómez Visuete, Hernany Josué (2023)
The present investigation was carried out in the province of Cotopaxi, where the specific objectives are to know the gastronomic tourism potential of the Sigchos canton, identify the current / potential market of gastronomic tourism in the canton and prepare a proposal for an academic article as a means of diffusion of the investigation in the RENPYS magazine, which bases the evaluation of gastronomic tourism in the study area, at the same time, for the collection of information, tourists and gastronomic service providers were taken into account. For the first objective, the evaluation of the gastronomic tourist potential was carried out, 14 preparations with gastronomic tourist potential of the Sigchos canton were determined, these preparations being: guinea pig, hornado, fritada, locro de zapallo, locro de zambo, zambo de dulce, runaucho, chicha de jora, guinea pig locro, chicken broth, yahuarlocro, natural juices with chicken eggs, panela and mortiño wine. Which, having met the criteria of: history and tradition, local ingredients, current tradition, offer to tourism, these being established by MINTUR and through the SIGAP traffic light methodology, obtained ratings between 75 and 100, which refers to the high potential of the gastronomic tourism of the Sigchos canton. The second objective was chosen the public that infers in the collection of data on the current / potential market of the Sigchos canton, through the sample calculation formula where 379 surveys were defined, which will be applied to local, national and international tourists focused on the gastronomic tourism, there it was verified that the current and potential profile of Sigchos is the nature tourism with the greatest demand by international tourists, mainly carrying out the activity of the Quilotoa Loop (trekking) passing through parishes such as Sigchos, Chugchilan, Isinlivi until reaching Quilotoa, During the trip they are happy to acquire the gastronomy and want to know more about the products used in it. As a third objective, a proposal for an academic article was idealized for the magazine "RENPYS" where the information collected was organized, which is an important dissemination tool that will strengthen the gastronomic cultural identity of Sigchos, maintaining updated information on its preparations and thus This can help future studies regarding the gastronomy of the place, at the same time that it would boost its economy.